To the evaluation of the carrying capacity of steel concrete beams on the basis of bent profiles - F. S. Zamaliev; A. G. Tamrazyan (Vestnik MGSU)
Introduction. Recently, more extensive use of steel-reinforced concrete (steel-concrete) structures is planned in civil buildings. In steel-reinforced concrete ceilings. The use of bent profiles in steel-reinforced concrete bent structures has not yet become widespread, probably due to the lack of simple methods. Therefore, the study of the stress-strain state of steel-reinforced concrete beams is a very urgent task. The article presents a new methodology and calculation formulas for assessing the bearing capacity of bent steel concrete elements reinforced with a cold-formed profile. Computer models of a composite beam consisting of bent profiles embedded in concrete are described, where options for the location of anchor ties are considered, which ensure the joint operation of both the profile with concrete and two bent channels into an I-beam. On the basis of the results of numerical studies, models of beams were made and tested. Analysis of the stress-strain state of experimental beams, their behavior under the influence of increasing the degree of increase in the intensity of development of the abilities of beams based on the limiting relative deformations of the personality of concrete. The results of experimental studies are presented in the form of graphs, comparison of the results of a full-scale experiment and numerical studies using computer models, as well as using analytical formulas. In conclusion, comparisons of the results of full-scale tests with numerical studies and by analytical formulas are given.Materials and methods. The ANSYS software package was used for computer simulation. Analytical formulas for assessing the strength of a bending element are written on the basis of the limiting relative compressive strains of concrete. For full-scale experiments, composite steel beams were made, consisting of bent channels with filling the side cavities with concrete, self-tapping screws were used as anchor connections.Results. The stress-strain state of the beams was revealed according to the obtained dependences and as a result of full-scale tests, as well as on the basis of computer simulation. The results of numerical studies are used for the manufacture of full-scale samples. The results of numerical values according to the proposed analytical formulas are compared with the data of full-scale experiments.Conclusions. Analytical dependences of the strength assessment of reinforced concrete bending elements by the method based on the limiting relative deformations of concrete compression are proposed, the features of the operation of reinforced concrete beams are studied by numerical modeling and by analytical dependences, full-scale experiments. It is shown that numerical studies give good convergence with experimental data. Analytical dependencies recorded on the basis of the ultimate relative compressive strains of concrete give better results than the well-known calculation method based on the limit force method.